ANALYSIS OF REGIONAL ORIGINAL REVENUE ACCOUNTING SYSTEM (PAD) OF THE ZAKAT SECTOR AT BPKD NORTH ACEH DISTRICT - Abdul Halim; Syawal Harianto; Haris Al Amin (RADJA PUBLIKA, 2022)
This study aims to determine the Zakat Sector Regional Original Income Accounting System at the Regional Financial Management Board (BPKD) of North Aceh Regency. This type of research is qualitative research. The data used are primary data in the form of interview results and secondary data in the form of financial reports and documents related to the financial data of the zakat sector's own-source revenue (PAD). Data collection techniques used were interviews and literature studies which were then analyzed using descriptive qualitative analysis methods. The results of the study show that the Zakat Sector Regional Original Revenue Accounting System (PAD) at the Regional Financial Management Board (BPKD) of North Aceh Regency has been carried out properly in accordance with the applicable laws and regulations.